Revision of the genus Filellum Hincks, 1868 (Lafoeidae, Leptothecata, Hydrozoa) - Marques, Antonio C.; Cantero, Álvaro L. Peña; Miranda, Thaís P.; Migotto, Alvaro E. (Zootaxa, 2011)
A taxonomic review of the cosmopolitan genus Filellum was performed considering morphology, morphometry and cnidome. Species for which we had access to materials were redescribed and morphologically characterized based on optical and scanning electron microscopy (SEM). The materials examined belong to museum collections, including type specimens. All records found in the literature were checked. Our analyses confirmed the validity of 10 out of the 18 nominal species referred to the genus, and established four others (F. adnatum, F. bouvieri, F. contortum and F. plicatum) as species inquirenda. A new species, Filellum bouvetensis sp. nov., is described. The species Reticularia annulata Watson, 1973, type species of the genus Corystolona Watson, 2002, has its type specimen referred to the genus Filellum, composing Filellum annulatum (Watson, 1973). We provide a key for the identification of the valid species of the genus Filellum.